2002
DOI: 10.1172/jci15334
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinases 2 and 9 work in concert to produce aortic aneurysms

Abstract: Matrix metalloproteinases (MMPs) 9 and 2 are increased in human abdominal aortic aneurysm (AAA) tissue, but their precise role and potential interaction remain unclear. Experimental induction of aortic aneurysms in mice genetically deficient in these peptidases could provide new insight into AAA pathogenesis. Mice deficient in the expression of MMP-9 (MMP-9KO) or MMP-2 (MMP-2KO) and their corresponding wild-type background mice (WT) underwent AAA induction by abluminal application of calcium chloride (CaCl 2 )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
347
2
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 504 publications
(360 citation statements)
references
References 32 publications
10
347
2
1
Order By: Relevance
“…A growing number of reports indicate that proteolytic breakdown of extracellular matrix by MMPs contribute to VSMCs migration 31. Moreover, mice deficient in MMP‐2 are actually resistant to aneurysm formation, indicating that MMP‐2 is a causative factor in the pathogenesis of AAA 17, 32. In line with this concept, in our study, we have seen significantly increased MMP‐2 levels in aneurysmatic tissue from our human and murine model of PPE‐induced AAA.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…A growing number of reports indicate that proteolytic breakdown of extracellular matrix by MMPs contribute to VSMCs migration 31. Moreover, mice deficient in MMP‐2 are actually resistant to aneurysm formation, indicating that MMP‐2 is a causative factor in the pathogenesis of AAA 17, 32. In line with this concept, in our study, we have seen significantly increased MMP‐2 levels in aneurysmatic tissue from our human and murine model of PPE‐induced AAA.…”
Section: Discussionsupporting
confidence: 85%
“…Migration into the neointima contributes to the progression of AAA. MMPs, especially MMP‐2, mediate extracellular matrix degradation and enable VSMCs migration 17. H 2 O 2 induces MMP‐2 expression in VSMCs and knockdown of VPO1 attenuates this effect (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the expression and activity of MMP-2 and MMP-9 are increased in human AAA, which are crucial to the formation of AAA. 20 In our study, we found that medium-dose Ang IV markedly increased collagen deposition in AAA by suppressing the expression and activity of MMP-2 and MMP-9, thus preserving the vascular integrity in ApoE −/− mice, whereas high-dose Ang IV did not have such a prohibitive effect on MMPs.…”
Section: Discussionsupporting
confidence: 45%
“…The near absence of MMP-9 expression following exposure of aortic concavity tissue to WSS proves to be an interesting phenomenon. Animal models have indicated that MMP-2 and MMP-9 work synergistically to promote aneurysm formation [49] and that MMP-9 knockout mice are unable to develop aneurysms even under the presence of increased MMP-2 activity [50] . Therefore, the absence of MMP-9 in fresh tissue and tissue subjected to TAV AA and BAV AA WSS, which prevents the possible downstream pathological effects of MMP-2/MMP-9 synergies, may protect the aortic wall against dilation and aneurysm formation.…”
Section: Tav and Lr-bav Hemodynamic Stresses Generate Similar Mmp Actmentioning
confidence: 99%